Utilization of Hatchery Waste Egg Flour as a Protein Source for Catfish (Clarias gariepinus) Fry - Assabri, Maulana Riski; Alim, Sahrul; Lumbessy, Salnida Yuniarti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Catfish (Clarias gariepinus) is one of the aquaculture commodities with high economic value. Its fast growth rate and broad environmental tolerance make it widely cultivated. This study aimed to analyze the growth performance of catfish (C. gariepinus) fry by using hatchery waste egg flour as a protein source in feed. The research employed an experimental method using a Completely Randomized Design (CRD) consisting of five treatments with three replications. Observed parameters included absolute weight, absolute length, specific growth rate (SGR), feed utilization efficiency (FUE), feed conversion ratio (FCR), and survival rate (SR). The results showed that adding hatchery waste egg flour had a substantial influence on absolute weight, SGR, FUE, and FCR, but not on absolute length or SR. The best treatment was the 50% substitution of fishmeal with hatchery waste egg flour, which resulted in an increase in absolute weight by 3.69 g, absolute length by 2.90 cm, SGR by 1.91%, and FUE by 59.30%. These findings indicate that hatchery waste egg flour can be used as an alternative protein source in feed for catfish fry.